Dynamic facade control systems for optimal daylighting, a case of Kerala - Govind Dev; Aysha Saifudeen (Sustainability Analytics and Modeling, 2023)
Natural daylighting of the building interiors contributes to better environmental quality and reduced energy consumption. Buildings in the tropical region require direct cut-off from irradiance to control internal thermal gain. More extensive fenestration may contribute towards more internal thermal gain because of an improper form of facade or shading systems, which may further contribute to the need for more cooling load in air conditioning. The commercial building sector consumes more energy due to the significance of aesthetics for interiors using artificial lighting techniques, especially during daytimes, and air conditioning due to increased thermal gains. This research intends to explore three basic types of dynamic facade systems, including folding, sliding and rotating types. The study is inclusive of the functional parameters, design and working mechanism of the selected systems, their impact on the illuminance and daylight factor, in the selected commercial building in Changanassery, Kerala, India. The authors calculated various angles of the selected location such as Solar Azimuth, Altitude, Horizontal Shadow Angle (HSA) and Vertical Shadow Angle (VSA), for further analysis. The tools used to do Building Information Modelling (BIM) of the prototype building, simulations of illuminance and daylight factor are Autodesk Revit, Autodesk Insight and Velux daylight visualizer respectively. The study concludes that the folding type of facade system is the most efficient type of dynamic facade system specific to the accurate prototype building location to ensure optimal daylighting while eliminating the undesirable effects of solar radiation.